(untitled) (Research Journal, 2025)
ICT stands for Information and Communication Technology and is outlined as a various set of technological tools and resources accustomed to communicating, and to make, publicize, store, and manage data. It is the kinds the method of teaching-learning and analysis though additional gripping, simple to understanding and every one comprising with a quicker presentation The use of ICT as pedagogy is to serve higher education to the entire world which gives prime quality education with high facilities to the learners so they become able to vie with the opposite pupils everywhere the world. The objective of this study is to explore the inevitability of ICT integrated pedagogy in the classroom. The study is descriptive in nature and thus the data presented relies on secondary sources. The use of ICT can enhance the exercise experiences of scholars. It additionally helps for building in career, in a very technology know-how world.